Amelioration of High Fructose Diet-Induced Insulin Resistance, Hyperuricemia, and Liver Oxidative Stress by Combined Use of Selective Agonists of PPAR-α and PPAR-γ in Rats - Mahmoud M. Farag; Ehab H. Ashour; Wessam F. El-Hadidy (Dubai Medical Journal)
Background: The use of high-fructose (Fr) corn sweeteners and sucrose in manufactured food has markedly increased recently. This excessive Fr intake has been proposed in the etiology of the metabolic syndrome, which shows an increasing prevalence throughout the world. Objective: In this study, we questioned whether fenofibrate (FF), a peroxisome proliferator-activated receptor (PPAR)-α agonist, and pioglitazone (PG), a PPAR-γ agonist, might be effective in ameliorating the metabolic syndrome in a rat model. Materials and Methods: The metabolic syndrome was induced by feeding rats a high-Fr (60%) diet for 10 weeks. The rats were divided into 5 groups: control group, fed a normal rat chow; Fr + vehicle group; Fr + FF group; Fr + PG group; and Fr + (FF + PG) group (treated with both drugs). Drug or vehicle treatment was given daily for 6 weeks (from weeks 5 to 10). Thereafter, blood and liver samples were obtained for biochemical studies. Results: Rats fed a high-Fr diet developed hyperglycemia, hyperinsulinemia, hyperuricemia, hypertriglyceridemia, and hypercholesterolemia, and had increased serum alanine aminotransferase, hepatic tumor necrosis factor-α, and malondialdehyde levels but decreases in both glutathione content and superoxide dismutase activity. Rat treatment with FF and/or PG attenuated these alterations. The improvement was greater with the combined treatment than with either drug alone, and normalization of insulin sensitivity was observed only in rats treated with the combination therapy. Conclusion: Acting on the 2 main PPAR subfamilies, the combination of FF and PG provides a more efficacious therapy for modulating the changes in serum insulin, uric acid, and lipids, as well as the accompanying hepatic inflammation and oxidative stress that characterize the Fr-induced metabolic syndrome.